Determinants of Household Food Security in Eastern Indonesia 2016-2023 - Muhammad Hartana Iswandi Putra; Ihda Nur Fathiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine the effect of education level, GRDP per capita, and the COVID-19 pandemic on household food security in Eastern Indonesia for the period 2016-2023, both partially and simultaneously. Food security is important because it not only concerns people's welfare but also influences a country's economy. The research method used in this study is a quantitative approach with the Ordinary Least Squares (OLS) method and annual time series data from 2016-2023. This study uses household food security as the dependent variable, education level and GRDP per capita as independent variables, and the COVID-19 pandemic as a dummy variable. The analytical technique used in this study is panel data regression analysis. The research findings illustrate that education level (X1) has a positive effect on household food security (Y). This means that the higher a person's education level, the higher their household food security will be. Vice versa. GRDP per capita (X2) has no effect on household food security (Y). This means that fluctuations in GRDP per capita in a region will not impact household food security (Y). The COVID-19 pandemic (X3) has a positive effect on household food security (Y). This means that if the COVID-19 pandemic occurs, household food security will increase. Vice versa. Education level, GRDP per capita, and the COVID-19 pandemic simultaneously influence household food security (Y).